The syntax of the sentence in Old Irish : selected studies from descriptive, historical, and comparative point of view - Mac Coisdealbha, Pádraig, 1949 or 1950-1976 (Buchreihe der Zeitschrift für celtische Philologie, 1998)
Old Irish is the language of Ireland in the period from the 8th to the 10th century AD, and is the oldest Celtic language well enough attested for adequate grammatical study. The book provides the only available detailed linguistic analysis of the syntactic structure of the Old Irish sentence. The basic form of the simple sentence, with the usual order of elements, verb-subject-object, is unproblematic from a synchronic viewpoint, but certain sentence types show more complex patterns of syntax, which have important implications for the typological, diachronic and comparative-historical analysis of Old Irish in particular, and Celtic and Indo-European languages in general. Sentence types which contain obligatory cataphoric pronouns referring to elements later in the same sentence are examined in detail, as well as constructions with marked initial topics, and the focussing construction of the cleft sentence. The approach is functional and typological, on the basis of a text corpus from the glosses on the Pauline epistles at Würzburg, with further material from Old Irish legal texts. The emphasis is on the communicative content and intent of the sentences of the corpus. The book is a newly edited version of MacCoisdealbha's Bochum dissertation of 1974, previously unpublished due to the author's death in 1976, and includes textual notes by the editor indicating progress, and indeed lack of progress, in the meantime, in areas covered by the book.